The extant ethnomedicines of six different hills of Eastern Ghats, South India - Santhanapandi, P.; Guruprasad, A.; Geetha, R.; Krithika, N.; Chittibabu, C. V. (Current Botany, 2022)
The extant ethnomedicines of the Eastern Ghats of south India were inventoried. The ethnobotanical survey conducted during the months of June to August 2018 in the six different hills of Eastern Ghats divulged a total of 54 (76%) medicinal plants belonging to 34 families being currently used by the herbal practitioners. The comprehensive details on the vernacular name, binomial, family, and plant part(s) used, and type of drug preparation of the ethnomedicines used for the various disease(s) are tabulated. The plant family Fabaceae (with five ethnomedicines) followed by Euphorbiaceae and Solanaceae (four each) were the dominant contributor in the Eastern Ghats. Interestingly, the same families were found contributing in similar pattern (nine and four each) in the literature pertaining to the Eastern Ghats, indicating their heritage and significance. Further, the ethnobotanical survey revealed that the leaves (25%) and paste form (46%) are the predominant plant part and drug type used respectively in the hills. The analysis also revealed the prevalent use of single drug (70%) and their overall depletion (24%) underlining the urgency to conserve them.